'Rijjool bak van Clio (begin cursus '98/99)'. Derde van rechts in het rijtuig Adama van Scheltema - Schuitvlot, Nic., (1898)
'Rijjool bak van Clio (begin cursus '98/99)'. Derde van rechts in het rijtuig Adama van Scheltema.